THE IMPACT OF BUILDING LAYOUT ON THE THERMAL ENVIRONMENT AT THE UNIVERSITY_ A CASE STUDY IN UITM PULAU PINANG CAMPUS - MOHD NASIR, SITI SHAREEDA; MOHD FOHIMI, NOR AZIRAH; HUSIN, NORASIKIN; MOHAMMUD, MOHD MAHADZIR; KOAY, MEI HYIE (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2024)
ABSTRACT - The university’s thermal environment affects the life of occupants in terms of their physical and mental health. Thermal environments are important factors in designing buildings in the university. The study was conducted in Universiti Teknologi MARA (UiTM) Cawangan Pulau Pinang, Permatang Pauh Campus buildings in a tropical region with a hot and humid climate. The purpose of this study is to analyze the influence of building layout on the surrounding thermal environment. The thermal environment parameters for every layout were investigated through field measurement. The results showed that the best building layout from the three selected building layout samples is the building layout at location C. Our findings reveal that building orientation at location C can lead to a 10% reduction in temperature fluctuations and increase air velocity by 70% and 5% increase in relative humidity. The building layout at location C has the best wind dispersion layout compared to the other building layout because it has a lot of open areas around the building. Building layout C also has the best heat dissipation because the layout of the building was not stacked with other buildings. Building layout C was in a location with good humidity that matches the human thermal comfort even in the climate of monsoon season in Malaysia during the end of the year December to January.